Tissue-Specific Transcriptomic Responses to Avian Reovirus Inoculation in Ovo - Zubair Khalid; Shahna Fathima; Ruediger Hauck (Viruses)
Avian reovirus (ARV) infections significantly impact the global poultry industry, but host responses across infection models remain poorly characterized. Using specific-pathogen-free chicken embryos, this study examined tissue-specific transcriptomic changes following in ovo inoculation with two doses of ARV S1133 at embryonic day 18. Quantitative PCR confirmed dose- and time-dependent viral replication, with the liver exhibiting the highest viral load at 24 h post-inoculation (hpi), whereas the kidneys, intestines, and bursa were only positive at 48 hpi with the higher viral dose. Transcriptomic profiling revealed the intestines mounted an extensive gene expression response, implicating early immune activation. Liver samples demonstrated strong upregulation of antiviral pathways, including interferon signaling and viral replication inhibition, while kidneys and intestines were enriched for coagulation and wound healing pathways. The bursae exhibited minimal immunity-related responses, suggesting insufficient maturation. Functional analyses confirmed tissue-specific immune and metabolic adaptations to infection. These findings indicate that ARV replication efficiency and host molecular responses are dose-, tissue-, and time-dependent. Notably, intestinal responses suggest preemptive immune engagement, while hepatic antiviral mechanisms may play a critical role in restricting viral spread. This study establishes foundational knowledge of host molecular responses to ARV in late-stage embryos, with implications for in ovo vaccination and early immunity.